A simple guide to IBM SPSS{u0CF4}atistics for version 23.0 - Kirkpatrick, Lee A., 1958-; Feeney, Brooke C., 1969- (Boston, Mass. : Cengage Learning, 2016)
'This no-nonsense book teaches you everything you need to know about the newest version of SPSS{u09AF}r Windows{u0CEF} you can effectively use the program in your statistic class. The guide's simple, straightforward style frees you to concentrate on learning basic statistical concepts, while still developing familiarity with SPSS. In no time, you will be using SPSS to do homework problems and conduct statistical analyses for research projects.'--Page 4 of cover.
Introduction to SPSS for Windows -- Entering data and naming variables -- Specifying analyses using the point-and-click method -- Specifying analyses using the Syntax Method -- Viewing and manipulating output -- Frequency distributions and descriptive statistics -- One-sample t-test -- Independent-samples t-test -- Dependent-samples (matched-pairs, paired samples) t-test -- One-way between-groups (independent groups) ANOVA -- Two-way between-groups (independent groups) ANOVA -- One-way within-participants (repeated measures) ANOVA -- Two-way mixed (between-within) ANOVA -- Correlations -- Simple regression -- Multiple regression -- Chi-square test of independence.
Keywords: SPSS for Windows; SPSS (Computer file).; Social sciences -- Statistical methods -- Computer programs; Statistics -- Computer programs; Statistics -- Data processing